The physical relationship between infectivity and prion protein aggregates is strain-dependent. - Philippe Tixador (Public Library of Science (PLoS), 2010)
Prions are unconventional infectious agents thought to be primarily composed of PrP(Sc), a multimeric misfolded conformer of the ubiquitously expressed host-encoded prion protein (PrP(C)). They cause fatal neurodegenerative diseases in both animals and humans. The disease phenotype is not uniform within species, and stable, self-propagating variations in PrP(Sc) conformation could encode this 'strain' diversity. However, much remains to be learned about the physical relationship between the infectious agent and PrP(Sc) aggregation state, and how this varies according to the strain. We applied a sedimentation velocity technique to a panel of natural, biologically cloned strains obtained by propagation of classical and atypical sheep scrapie and BSE infectious sources in transgenic mice expressing ovine PrP. Detergent-solubilized, infected brain homogenates were used as starting material. Solubilization conditions were optimized to separate PrP(Sc) aggregates from PrP(C). The distribution of PrP(Sc) and infectivity in the gradient was determined by immunoblotting and mouse bioassay, respectively. As a general feature, a major proteinase K-resistant PrP(Sc) peak was observed in the middle part of the gradient. This population approximately corresponds to multimers of 12-30 PrP molecules, if constituted of PrP only. For two strains, infectivity peaked in a markedly different region of the gradient. This most infectious component sedimented very slowly, suggesting small size oligomers and/or low density PrP(Sc) aggregates. Extending this study to hamster prions passaged in hamster PrP transgenic mice revealed that the highly infectious, slowly sedimenting particles could be a feature of strains able to induce a rapidly lethal disease. Our findings suggest that prion infectious particles are subjected to marked strain-dependent variations, which in turn could influence the strain biological phenotype, in particular the replication dynamics.